2019
DOI: 10.1007/s10295-018-02123-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of AoD9D enhances salt tolerance with increased accumulation of unsaturated fatty acid in transgenic Saccharomyces cerevisiae

Abstract: Salt stress can trigger several physiological responses in microorganisms such as the increasing accumulation of unsaturated fatty acid, which was biosynthesized by delta-9 fatty acid desaturases (D9D) at the first step. In the present study, two D9D genes, designated AoD9D1 and AoD9D2, were isolated from Aspergillus oryzae. The expression analysis showed that AoD9D1 and AoD9D2 were upregulated under salt stress. To investigate the function of AoD9D, transgenic Saccharomyces cerevisiae strains that heterologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The synthesis of UFAs is regulated during changing environmental conditions, and the UFAs play a crucial role in environmental adaptation in a broad range of organisms from microorganisms to animals and plants ( Wada et al, 1990 ; Miquel et al, 1993 ; Svensk et al, 2013 ; Yancey, 2020 ; Zhang Z. et al, 2020 ). It has been widely reported that there were more UFAs in salt-tolerant plants, yeast as well as bacterial cells ( de Carvalho et al, 2014 ; Guo et al, 2019 ; Li et al, 2019 ). Moreover, Lucu et al (2008) reported that UFAs might be important during the acclimation of the shore crab Carcinus aestuarii to hypoosmotic condition.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of UFAs is regulated during changing environmental conditions, and the UFAs play a crucial role in environmental adaptation in a broad range of organisms from microorganisms to animals and plants ( Wada et al, 1990 ; Miquel et al, 1993 ; Svensk et al, 2013 ; Yancey, 2020 ; Zhang Z. et al, 2020 ). It has been widely reported that there were more UFAs in salt-tolerant plants, yeast as well as bacterial cells ( de Carvalho et al, 2014 ; Guo et al, 2019 ; Li et al, 2019 ). Moreover, Lucu et al (2008) reported that UFAs might be important during the acclimation of the shore crab Carcinus aestuarii to hypoosmotic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the results in our study, it is worth trying that overexpression of the Cns1 / Cns2 or Cns1 / Cns2 / Cns3 fusion gene via individually transformed the control strain of C. militaris under salt treatment. Furthermore, it has been reported that several genes can regulate osmoadaptation, such as salt-tolerant gene HOG and fatty acid metabolism gene delta-9 fatty acid desaturases ( 56 , 57 ). Thus, it can be expected that the obtaining of industrial strains possesses salt tolerance and high cordycepin production via overexpression of the cordycepin biosynthetic gene and salt-tolerant gene.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome b 5 proteins have been found to be involved in fatty acid desaturation ( Takashi et al, 1972 ). For instance, Li et al (2019) transformed Cyt-b 5 domain of the delta-9 fatty acid desaturase from A. oryzae into S. cerevisiae and the transformed strains showed enhanced accumulation of unsaturated fatty acid and stronger salt tolerance than the wild type. Similarly, our results here showed that Δ plcb5l1 mutants were more sensitive to the salt stress caused by NaCl and CaCl 2 ( Figure 6 ), which might be caused by the disruption of fatty acid desaturation in the Δ plcb5l1 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cytochrome P450s and the cytochrome b 5 reductase-cytochrome b 5 system have been reported to play an important role in the synthesis of sterols in fungi, which are indispensable for fungal hyphal growth and asexual sporulation ( Lamb et al, 1999 ; Derbyshire et al, 2015 ). In Saccharomyces cerevisiae , heterologous expression of Aspergillus oryzae D9D genes, AoD9D1 and AoD9D2 , which encode proteins containing fatty acid desaturase and Cyt-b 5 domain, contribute to the accumulation of unsaturated fatty acid and tolerance of high salinity stress depending on both the fatty acid desaturase and Cyt-b 5 domain ( Li et al, 2019 ). However, our knowledge of the function of Cyt-b 5 domain proteins in plant pathogenic oomycetes is still lacking.…”
Section: Introductionmentioning
confidence: 99%